PERAN BANK SYARIAH INDONESIA (BSI) DALAM MENDORONG PERTUMBUHAN INDUSTRI HALAL DI INDONESIA - Faricha Lita Nabbila; Andriani; Dewi Fatmala Putri; Widya Ratna Sari (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
Indonesia is a country with the 4th ranking for the halal industry in the world with a majority Muslim population which is considered less optimal in managing the growth of the halal industry compared to other countries in various sectors. This research aims to examine whether the existence of BSI can encourage the growth of the halal industry in Indonesia. The method applied in this research is a descriptive method with a qualitative descriptive research type, which utilizes a literature study approach. The research results show that. BSI has distributed financing to the halal value chain sector Rp. 18 trillion, consisting of financing for the halal food and beverage subsector Rp. 9 trillion, pharmaceuticals and cosmetics Rp. 7 trillion, and fashion and fashion Rp. 3 trillion. Carrying out MSME development programs through the Sharia KUR Recipient MSME Program, BSI UMKM Center, and BSI Entrepreneurial Talent Competition